ANALISIS NIAT KUNJUNGAN KEMBALI WISATAWAN KE DESA WISATA MELALU PENDEKATAN PRODUK WISATA - Herman, Herman; Achlan Fahlevi Royanow,; Hamsu Hanafi, (Journal of Innovation Research and Knowledge, 2025)
Tourism villages have emerged as increasingly popular destinations among travelers. The tourism products offered are crucial in attracting tourists' intentions to revisit. This study aims to analyze the impact of tourism products—specifically culinary offerings, natural scenery, local friendliness, and tourist activities—on tourists' intentions to revisit the Kembang Kuning Tourism Village. Employing a quantitative approach with a cross-sectional study design, data were collected through the distribution of questionnaires to 100 respondents. Data analysis was performed using multiple linear regression, with validity and reliability tests conducted using IBM SPSS Statistics Version 26. The findings indicate that culinary offerings (X1) and natural scenery (X2) do not have a significant effect on the intention to revisit. In contrast, local friendliness (X3) and tourist activities (X4) have a significant impact. Based on these results, it is recommended that the Kembang Kuning Tourism Village enhance the quality of its culinary offerings and manage natural tourist attractions to align with tourists' needs and expectations, thereby positively influencing their intention to return